Peran dan Tanggungjawab Data Protection Officer dalam Pelaksanaan Perlindungan Data Pribadi - Hikmawan Ajiraga (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
One consequence of rapid progress in technology and information today is the need to safeguard privacy, especially regarding personal data. To support efforts to protect personal data, a party is needed to monitor and ensure compliance with data processing regulations, known as the Data Protection Officer (DPO). Regulations about DPOs are mainly outlined in Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), which has been in effect since October 2024. However, these regulations remain broad and lack specific clarity about the DPO's role, creating a legal gap. Additionally, the Draft Government Regulation (RPP), which would implement the PDP Law, has yet to be ratified. Given these issues, this article will explore the current state of DPO regulation in Indonesia and compare it with practices in the European Union through the European Union General Data Protection Regulation (EU GDPR).